Effects of Ventilator-Associated Pneumonia Among Saudian's Critically Ill Patients, Systemic Review. Issue 3 (25th June 2022) - M., E. H.; Althubity, Althubity; W., S.; Abdullah, Abdullah; S., A.; Aljuaid, Aljuaid; S., F. M.; Altalhi, Altalhi; A., M.; Althagfi, Althagfi; M., S.; Alzaidi, Alzaidi; et al.
No abstract available